Psychometric studies of instruments in Spanish for the detection of common mental disorders: A review. - Vega-Dienstmaier, Johann M. (2022)
The objective of this review is to describe the psychometric characteristics of the Spanish versions of instruments for the detection of common mental disorders, on the basis of a systematic search carried out in PubMed and Google Scholar. The following instruments with pertinent psychometric information were identified: General Health Questionnaire (GHQ-12 and GHQ-28), Hospital Anxiety and Depression Scale (HADS), Personal Health Scale (PHS), Self-Reporting Questionnaire (SRQ -20), Kessler Psychological Distress Scale (K-6 and K-10), Patient Health Questionnaire (PHQ), Edinburgh Scale (EPDS), Dep5, Anx5 and Symptom Checklist (SCL-90 and SCL-90-R). The most studied instruments were GHQ and HADS. Most of the studies were carried out in Spain. In Peru, SRQ-20, PHS, K-6, K-10 and GHQ-28 were evaluated. The psychometric properties described include internal consistency, factorial structure, area under the Receiver Operating Characteristic curve (AUC), sensitivity, specificity and Youden index (J). J of the instruments were between 0.2389 and 0.767, and the AUC, between 0.758 and 0.933. This review could help to choose psychometric instruments in Spanish for studies and clinical practice, as well as to systematically identify research needs about this topic.